Peptide based nano-drug candidate for cancer treatment: Preparation, characterization, in vitro and in silico evaluation - Bicak, Bilge; Budama-Kilinc, Yasemin; Kecel-Gunduz, Serda; Zorlud, Tolga; Akman, Gizem (ELSEVIER, 2021)
Tyrosyllysylthreonine (YKT) tripeptide has antibacterial, antiviral, anticancer and antioxidant properties based on the properties of the amino acids Tyrosine, Lysine and Threonine in its structure. The aim of this study is to design a peptide-based nano-drug candidate and to increase the effectiveness of the tripeptide and prevent its adverse effects. In this purpose, YKT loaded chitosan nanoparticles (CNPs) were synthe-sized by using a modified version of the ionic gelation method. The nanoparticles were characterized with various techniques such as Dynamic Light Scattering (DLS), UV-Vis, FTIR-ATR. Besides, scanning electron microscopy (SEM) was used to investigate the morphology of the nanoparticles. In addition, the in vitro cytotoxicity of YKT peptide and YKT loaded CNPs were comparatively examined on the Rat prostate can-cer (MAT-Lylu) cell line. Moreover, in silico studies were conducted via theoretical methods such as MD, Molecular docking and ADME (Absorption, Distribution, Metabolism and Excretion) analysis. In conclu-sion, in vitro cell culture and in silico molecular docking studies were performed for YKT loaded CNPs in order to contribute to design of peptide based controlled release system for use in cancer therapy. It was discussed whether YKT loaded CNPs may use as nano-drug for prostate cancer treatment. (c) 2021 Elsevier B.V. All rights reserved.
Keywords: Drug; nanoparticle; peptide; anti-cancer; molecular docking; ADME; N-ALKYL SULFATES; CHITOSAN NANOPARTICLES; DELIVERY SYSTEMS; ACCURATE DOCKING; ANTIOXIDANT; VITRO; IDENTIFICATION; ANTIBACTERIAL; KYOTORPHIN; COMPLEXES; Chemistry